# I'm not sure if I have this correct I have to solve each literal equation for the indicated variable. A=1/2h(B+b)variable is (b). I have the answer as:

2A=h(B1+b2)

2A/h=B1+b2

(2A/h)-b2=B1

Is this correct?

weren't you supposed to solve for "b"?

that would be

b = (2A - Bh)/h or 2A/h - B

(looks similar in pattern to your last line)

## Yes, you are correct. The equation A = (1/2)h(B + b) can be solved for the variable b. Here's how you can solve it step by step:

1. Distribute the 1/2 to both terms inside the parentheses:

A = (1/2)hB + (1/2)hb

2. Move the (1/2)hB term to the other side of the equation by subtracting it from both sides:

A - (1/2)hB = (1/2)hb

3. Multiply both sides of the equation by 2 to eliminate the fraction:

2(A - (1/2)hB) = hb

4. Distribute the 2 on the left side:

2A - hB = hb

5. Now, isolate the variable b by subtracting hb from both sides:

2A - hB - hb = 0

6. Factor out b on the left side:

2A - (h + 1)b = 0

7. Divide both sides of the equation by (h + 1) to solve for b:

b = (2A - hB) / (h + 1)

So, the correct answer for solving the equation A = (1/2)h(B + b) for b is:

b = (2A - hB) / (h + 1)

Your answer of b = (2A/h) - b2 is incorrect. Make sure you carefully distribute and isolate the variables to get the desired solution.

## Your initial answer is incorrect.

To solve the literal equation A = (1/2)h(B + b) for the variable b, you can follow these steps:

1. Distribute the 1/2h to the terms inside the parentheses: A = (1/2)hB + (1/2)hb

2. Subtract (1/2)hB from both sides of the equation to isolate the term with b: A - (1/2)hB = (1/2)hb

3. Divide both sides of the equation by (1/2)h to solve for b: (A - (1/2)hB) / ((1/2)h) = b

4. Simplify the expression on the left-hand side: 2(A - (1/2)hB) / h = b

5. Further simplify the expression: (2A - hB) / h = b

Therefore, the correct answer is b = (2A - hB) / h.